Respuesta :
when you multiply exponents, Your add them so you need to add 4 and 2 to get 6. The answer would be C
we have
[tex](5a^{2} b^{3} )(6a^{k}b)=30 a^{6}b^{4}[/tex]
Multiply the left side and then compare with the right side
[tex](5a^{2} b^{3} )(6a^{k}b)[/tex]
Combine like terms
[tex](5*6)(a^{2}*a^{k})(b^{3}*b)\\=(30)(a^{k+2})(b^{4})[/tex]
Compare with the right side
[tex](30)(a^{k+2})(b^{4})=30 a^{6}b^{4}[/tex]
so
[tex](a^{k+2})=a^{6}[/tex]
[tex]k+2=6[/tex]
solve for k
[tex]k=6-2=4[/tex]
therefore
the answer is the option C
[tex]4[/tex]